2012
DOI: 10.5539/ijps.v4n2p42
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Patients' Adherence to Medication and Lifestyle Change Recommendations: Data from Canada

Abstract: The purpose of this study was to investigate factors related to patients' adherence to prescribed medications and recommended lifestyle changes. Two hundred and ninety-eight adults from a northern Canadian community filled out a questionnaire. Several intriguing findings emerged: (a) Adherence to lifestyle changes and participants' age presented a U-shape relationship; (b) Those who perceived themselves to be in poor health were less likely than those in good health to adhere to lifestyle changes; (c) Barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 61 publications
(105 reference statements)
4
29
2
3
Order By: Relevance
“…Their preferred health message disseminator was, in order of preference, a doctor, nurse, other health professional and trained community members (community health care workers). This may be as a result of the fact that these health professionals are regarded as having expertise in health matters confirming the findings of Parker, Steyn, Levitt, and Lombard (2012), Parajuli, Saleh, Thapa, and Ali (2014) and Levesque et al (2012). These authors found that adherence to interventions worked better when the doctor is the source of the information as this allowed patients to build a relationship with the person disseminating the health messages and facilitated discussing their problems.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Their preferred health message disseminator was, in order of preference, a doctor, nurse, other health professional and trained community members (community health care workers). This may be as a result of the fact that these health professionals are regarded as having expertise in health matters confirming the findings of Parker, Steyn, Levitt, and Lombard (2012), Parajuli, Saleh, Thapa, and Ali (2014) and Levesque et al (2012). These authors found that adherence to interventions worked better when the doctor is the source of the information as this allowed patients to build a relationship with the person disseminating the health messages and facilitated discussing their problems.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, previous research showed that the implementation of, and adherence to lifestyle changes are influenced by people's social environment and personal characteristics (Levesque, Li, & Pahal, 2012;Mayega, Etajak, Rutebemberwa, Tomson, & Kiguli, 2014;Muchiri, Gericke, & Rheeder, 2012;Steyl & Phillips, 2014). Participants also questioned the benefits of health interventions probably because of clearly visible consequences of not conforming to recommended actions not being disseminated.…”
Section: Discussionmentioning
confidence: 99%
“…The environment, according to SCT, influences behavior and determines opportunities for behavior change (Bandura, 1998). Consistent with previous research (Levesque et al, 2012), participants discussed the patient-provider relationship and specific activities to achieve an effective relationship as distinct contributors to adherence. High quality relationships are defined as those that are collaborative in nature and foster a sense of trust (Ratanawongsa et al, 2013).…”
Section: Discussionmentioning
confidence: 72%
“…Research has examined the influence of personal determinants of health on participation in and adherence to health-promoting behavior. Behaviors, such as healthy eating and self-care, have been found to be positively affected by motivation to change (Centis et al, 2014), social support (Levesque, Li, & Pahal, 2012), personality (Lunn, Nowson, Worsley, & Torres, 2014), and self-worth and self-esteem (Huberty et al, 2014). Though, motivation and self-efficacy have also been described as important barriers to diabetes care by both patients and providers (Simmons, Lillis, Swan, & Haar, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, about a quarter of all respondents reported perceived harm as a result of a drug-alcohol interaction, including serious consequences such as hospital admission and worsening of their psychiatric conditions. The current study did not explore reasons why participants did not follow advice from health care professionals, but we hypothesize the following: challenges associated with avoiding alcohol completely when taking an interacting medication for a chronic condition, lack of a strong therapeutic alliance between the provider and patient, 13 inadequate health literacy, insufficient time for proper counselling, and emotional barriers involving selfmedication. Future studies should explore these hypotheses to…”
Section: Resultsmentioning
confidence: 99%